Effect of Phosphorus Fertilization on Phytoremediation efficacy of Heavy Metals by Wheat and Bean Plants - snds bashir (Zanco Journal of Pure and Applied Sciences, 2019)
A pot experiment was con ducted at the experimental farm of Halabja Technical College of Applied Sciences in July 2017 to July 2018, 2 km north of Halabj a city in the longitude 45°59'40"E and latitude 35°10'28"N. To determine the impact of the use of phytoremedial techniques in the governorate of Halabja on contaminated soil with heavy metals. Soil samples were collected randomly from 15 sites within the solid waste dumping area and control sample, These samples were analyzed for chemical characteristics and concentration of certain heavy metals such as Lead (Pb), Cadmium (Cd), Nickel (Ni), Zinc (Zn) and Iron (Fe) using ICP-MS (inductively coupled plasma mass spectrometer. The summary of the main results was as follow maximum concentration of heavy metals from soil in bean plant were (Pb and Ni) were (55.4 and 50.1 %) for (TSP 40), (Fe and Cd) were (49.7 and 44.5 %) for (TSP 160) and uptake of Zn increased by (45.6 %) for (TSP 120) compared to control treatment, while wheat plant extracted heavy metals (Pb, Cd, Ni, Fe, and Zn) by (60.6, 53.4, 37.1, 37.1, and 26.6 %) respectively for (TSP 160) compared with control treatment. These results evidence that Phytoextraction of (Pb, Cd, Ni, Zn, and Fe) by (Bean) plant was much greater than that by (Wheat) from municipally polluted soil after adding phosphorus fertilizer to the soil. This study confirms that (Bean) as one of the plants that could be employed in phytoremediation of soil polluted by heavy metals.